TRNA‐derived small RNA, 5'tiRNA‐Gly‐CCC, promotes skeletal muscle regeneration through the inflammatory response. Issue 2 (8th February 2023) - Shen, Linyuan; Liao, Tianci; Chen, Qiuyang; Lei, Yuhang; Wang, Linghui; Gu, Hao; Qiu, Yanhao; Zheng, Ting; Yang, Yiting; Wei, Chenggang; Chen, Lei; Zhao, Ye; et al.
Abstract: Background: Increasing evidence shows that tRNA‐derived small RNAs (tsRNAs) are not only by‐products of transfer RNAs, but they participate in numerous cellular metabolic processes. However, the role of tsRNAs in skeletal muscle regeneration remains unknown. Methods: Small RNA sequencing revealed the relationship between tsRNAs and skeletal muscle injury. The dynamic expression level of 5'tiRNA‐Gly after muscle injury was confirmed by real‐time quantitative PCR (q‐PCR). In addition, q‐PCR, flow cytometry, the 5‐ethynyl‐2'‐deoxyuridine (Edu), cell counting kit‐8, western blotting and immunofluorescence were used to explore the biological function of 5'tiRNA‐Gly. Bioinformatics analysis and dual‐luciferase reporter assay were used to further explore the mechanism of action under the biological function of 5'tiRNA‐Gly. Results: Transcriptome analysis revealed that tsRNAs were significantly enriched during inflammatory response immediately after muscle injury. Interestingly, we found that 5'tiRNA‐Gly was significantly up‐regulated after muscle injury ( P <  0.0001) and had a strong positive correlation with inflammation in vivo. In vitro experiments showed that 5'tiRNA‐Gly promoted the mRNA expression of proinflammatory cytokines ( IL‐1β, P =  0.0468; IL‐6, P =  0.0369) and the macrophages of M1 markers ( TNF‐α, P =  0.0102; CD80, P =  0.0056; MCP‐1, P =  0.0002). On the contrary, 5'tiRNA‐Gly inhibited the mRNA expression of anti‐inflammatory cytokines ( IL‐4, P =  0.0009; IL‐10, P =  0.0007; IL‐13, P =  0.0008) and the mRNA expression of M2 markers ( TGF‐β1, P =  0.0016; ARG1, P =  0.0083). Flow cytometry showed that 5'tiRNA‐Gly promoted the percentage of CD86 + macrophages (16%, P =  0.011) but inhibited that of CD206 + macrophages (10.5%, P =  0.012). Immunofluorescence showed that knockdown of 5'tiRNA‐Gly increased the infiltration of M2 macrophages to the skeletal muscles (13.9%, P =  0.0023) and inhibited the expression of Pax7 ( P =  0.0089) in vivo. 5'tiRNA‐Gly promoted myoblast the expression of myogenic differentiation marker genes ( MyoD, P =  0.0002; MyoG, P =  0.0037) and myotube formation (21.3%, P =  0.0016) but inhibited the positive rate of Edu (27.7%, P =  0.0001), cell viability (22.6%, P =  0.003) and the number of myoblasts in the G2 phase (26.3%, P =  0.0016) in vitro. Mechanistically, we found that the Tgfbr1 gene is a direct target of 5'tiRNA‐Gly mediated by AGO1 and AGO3. 5'tiRNA‐Gly dysregulated the expression of downstream genes related to inflammatory response, activation of satellite cells and differentiation of myoblasts through the TGF‐β signalling pathway by targeting Tgfbr1 . Conclusions: These results reveal that 5'tiRNA‐Gly potentially regulated skeletal muscle regeneration by inducing inflammation via the TGF‐β signalling pathway. The findings of this study uncover a new potential target for skeletal muscle regeneration treatment.